The special appeal and the question of of law and fact: Summary 7/STJ (Revista do Tribunal Regional Federal da 3ª Região, 2019)
The purpose of this article is to examine the analysis of “matters of fact” and “matters of law”, based on what is said by Summary 7/STJ, and investigate the difference between two issues for the purpose of fitting the special appeal.
Keywords: special appeal; admissibility; STJ; matters of fact; matters of law; summary 7/STJ